Penggunaan Ragam Bahasa Sarkasme pada Kolom Komentar Akun Tiktok @Vadelbadjideh - Nur Fadilah; Ari Nugrahani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the types of sarcasm found in the comment section of the TikTok account @vadelbadjideh, the types of posts that receive the most sarcastic comments, and the illocutionary speech acts contained in those comments. The research method used is descriptive qualitative, employing documentation techniques by capturing screenshots of comments from the most viewed video posts. The data were analyzed using a pragmatic approach based on Charles Morris’s theory and classified according to Elizabeth Camp’s sarcasm types and Searle’s speech act categories. The results show that lexical sarcasm is the most commonly used form by netizens, followed by propositional sarcasm, sarcasm with the word "like," and illocutionary sarcasm. Viral and controversial posts—such as videos featuring unique movements or connections to public issues—attract the highest number of sarcastic responses. The most frequent illocutionary acts found are assertive and expressive types, indicating that social media users employ sarcasm to express opinions and emotions. This research contributes to understanding the dynamics of digital communication and the role of sarcasm in shaping social interactions on social media platforms.